2018
DOI: 10.1016/j.celrep.2018.02.088
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Release Site Clearance within the Active Zone by Reduced SCAMP5 Expression Causes Short-Term Depression of Synaptic Release

Abstract: Despite being a highly enriched synaptic vesicle (SV) protein and a candidate gene for autism, the physiological function of SCAMP5 remains mostly enigmatic. Here, using optical imaging and electrophysiological experiments, we demonstrate that SCAMP5 plays a critical role in release site clearance at the active zone. Truncation analysis revealed that the 2/3 loop domain of SCAMP5 directly interacts with adaptor protein 2, and this interaction is critical for its role in release site clearance. Knockdown (KD) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…They are implicated in a variety of membrane trafficking events. SCAMP5 is enriched in the brain with selective functions in synaptic vesicle trafficking 15. Zhao et al 16 carried out a SCAMP5 knockdown experiment showing that SCAMP5 functions to control the synaptic vesicles recycling machinery when neuronal activity is high enough to impose a heavy load on endocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are implicated in a variety of membrane trafficking events. SCAMP5 is enriched in the brain with selective functions in synaptic vesicle trafficking 15. Zhao et al 16 carried out a SCAMP5 knockdown experiment showing that SCAMP5 functions to control the synaptic vesicles recycling machinery when neuronal activity is high enough to impose a heavy load on endocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…They also conclude that SCAMP5 may recruit or promote the assembly of endocytic components to maintain an adequate number of endocytic machines during sustained neuronal activity. A recent study by Park et al 15 demonstrated that SCAMP5 plays an important role in release site clearance during intense neuronal activity and that loss of SCAMP5 results in a traffic jam at release sites, causing aberrant short-term synaptic depression that might be associated with the synaptic dysfunction observed in autism. At the molecular level, SCAMP5 has also been shown to interact both with SLC9A7 and with the synatotagmins SYT1 and SYT2,17 18 which are important for synaptic vesicle fusion.…”
Section: Discussionmentioning
confidence: 99%
“…SCAMP proteins were first characterized in mammals for their role in endocytosis (Fernández-Chacón et al, 2000). Current insights in the animal and plant field show a broader function of SCAMPs in plasma membrane phase separation, cell plate formation, and pathogen-induced stomatal closure (Bourdais et al, 2019;Lam et al, 2008;Park et al, 2018). SCAMP5 was also previously identified to reside in close proximity to TPC by proximity labelling (Arora et al, 2020).…”
Section: The First Eh Domain Recognises a Novel Retrograde Transport mentioning
confidence: 99%
“…Cultures of cortical or hippocampal neurons were prepared from P0-P2 neonatal mouse brains as previously described (Ferguson et al, 2007, Park, Lee et al, 2018 and used at DIV14-23. For lenti-virus infection, DIV3 neurons cultured on 12-mm coverslips were infected with 1 μl FUGW-GFP-Sac2 viruses (5E9 Integration Unit (IU)/mL) and fixed after DIV16.…”
Section: Primary Neuronal Culture and Fluorescence Microscopymentioning
confidence: 99%
“…For lenti-virus infection, DIV3 neurons cultured on 12-mm coverslips were infected with 1 μl FUGW-GFP-Sac2 viruses (5E9 Integration Unit (IU)/mL) and fixed after DIV16. Calcium phosphate transfection was performed as previously described (Park et al, 2018). Cells were fixed with 4% formaldehyde [freshly prepared from paraformaldehyde (PFA)] in 0.1 M sodium phosphate pH 7.2 and 4% sucrose, blocked and permeabilized with PBS containing 5% bovine serum albumin (BSA) and 0.1% triton X-100.…”
Section: Primary Neuronal Culture and Fluorescence Microscopymentioning
confidence: 99%